2018
DOI: 10.1111/jgs.15394
|View full text |Cite
|
Sign up to set email alerts
|

Is a Decline in Will to Live a Consequence or Predictor of Depression in Late Life?

Abstract: Our results indicate that WTL predicts DS rather than vice versa, suggesting that decline in WTL contributes and leads to depression at present and in future. Health strategies designed to promote WTL in older adults may help forestall depression. Moreover, psychotherapeutic interventions targeting WTL might be effective in the treatment of depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 35 publications
2
23
0
1
Order By: Relevance
“…This gender difference has also been established in another research (Carmel et al, 2007(Carmel et al, , 2018.…”
Section: Will-to-livesupporting
confidence: 69%
See 2 more Smart Citations
“…This gender difference has also been established in another research (Carmel et al, 2007(Carmel et al, , 2018.…”
Section: Will-to-livesupporting
confidence: 69%
“…These constructs were selected as they are conceptually linked to WTL (Carmel, 2017). Additionally, as past investigation showed that elderly women express significantly weaker WTL than elderly men (Carmel, 2001;Carmel et al, 2007Carmel et al, , 2018, we also analyzed the relationship between gender and WTL in an adolescent population.…”
Section: The Present Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Women's biological features, such as hormonal changes, along with their disadvantages in societal areas of life (socioeconomic status, gender-related social roles) extend to gender differences in mental health. Thus, women tend to report being more moody than men (91), more worried (92), more anxious (93, 94), and more stressed and depressed (11, 68, 82, 87, 95100). Many studies have also shown that women score lower than men on psychological indicators of well-being and coping resources, such as self-esteem (10, 99, 101104), will-to-live (9, 11), and self-efficacy (23).…”
Section: Gender Differences In Well-beingmentioning
confidence: 99%
“…will-to-live reflected the well-being of older people and closely associated with health and wellbeing of the elderly [26][27][28][29] . Compared to previous studies on desires and will-to-live focusing on the older people [26][27][28][29][30][31][32][33], our study had a good sampling frame to achieve the representativeness of the overall population in the country, and by applying plenty of questions that were designed to scrutinize various aspects of people's life and social security issues, we were able to examine the effects of diverse covariates in details.…”
Section: Plos Onementioning
confidence: 99%